2006
DOI: 10.1097/01.acm.0000246756.55626.1b
|View full text |Cite
|
Sign up to set email alerts
|

The Israel Center for Medical Simulation: A Paradigm for Cultural Change in Medical Education

Abstract: Simulation-based medical education (SBME) is a rapidly growing field, as is illustrated by the increased development of simulation centers worldwide. SBME is becoming a powerful force in addressing the need to increase patient safety through quality-care training. Recognizing the benefits of SBME, increasing numbers of bodies involved in medical and health care education and training are establishing simulation centers worldwide. The general model of most facilities focuses on a single simulation modality or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 29 publications
1
39
0
4
Order By: Relevance
“…[5][6][7][8] Multiple authors have suggested the use of simulation in teaching and assessing resident competency in procedures, hypothesizing that it improves patient safety and the quality of care. [9][10][11][12][13][14][15][16] Although the best model for practical FAST instruction has not been determined, the requirement to incorporate bedside ultrasound (US) education in emergency medicine curricula has resulted in the development of US simulation software. Few studies have examined the effectiveness of multimedia simulation in teaching FAST image interpretation, 17 and no studies have examined its effectiveness in teaching image acquisition.…”
mentioning
confidence: 99%
“…[5][6][7][8] Multiple authors have suggested the use of simulation in teaching and assessing resident competency in procedures, hypothesizing that it improves patient safety and the quality of care. [9][10][11][12][13][14][15][16] Although the best model for practical FAST instruction has not been determined, the requirement to incorporate bedside ultrasound (US) education in emergency medicine curricula has resulted in the development of US simulation software. Few studies have examined the effectiveness of multimedia simulation in teaching FAST image interpretation, 17 and no studies have examined its effectiveness in teaching image acquisition.…”
mentioning
confidence: 99%
“…Similar studies have found positive results (81). Although VR laparoscopy is resource-intensive, simulation is widely used for skill acquisition (79) and can be a dominant mode for medical education (100).…”
Section: Interventions Around the Caregiver Educationmentioning
confidence: 77%
“…35 Dynamic variation during emergency scenarios can be used to test the integration of knowledge (e.g., sudden loss of airway scenarios in a polytrauma patient in the Acute Trauma Life Support course moulage). 36 From an ethical point of view, Ziv et al 37 have argued that doctors have a moral imperative to ensure patients get the highest quality of care and should not be treated by those who have not shown that they can perform the task safely and reliably. Such thinking will inevitably lead to its increased use in training and examination.…”
Section: Advantages Of Simulation and Integration With Learning Theoriesmentioning
confidence: 99%